2019
DOI: 10.1192/bjp.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health problems in schools: poverty and other risk factors among 28 000 adolescents in England

Abstract: SummaryCurrent mental health provision for children is based on estimates of one in ten children experiencing mental health problems. This study analyses a large-scale community-based dataset of 28 160 adolescents to explore school-based prevalence of mental health problems and characteristics that predict increased odds of experiencing them. Findings indicate the scale of mental health problems in England is much higher than previous estimates, with two in five young people scoring above thresholds for emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(135 citation statements)
references
References 15 publications
6
116
0
13
Order By: Relevance
“…The finding of our study is consistent with the view that girls have a higher risk of experiencing mental health problems than boys [5,41,42]. The older age groups reported significantly higher risk of psychological symptoms, which was in line with previous surveys in England [43]. Our study showed that students from low-income families were more prone to be distressed by psychological symptoms, which was in agreement with previous researches [44][45][46][47].…”
Section: Discussionsupporting
confidence: 93%
“…The finding of our study is consistent with the view that girls have a higher risk of experiencing mental health problems than boys [5,41,42]. The older age groups reported significantly higher risk of psychological symptoms, which was in line with previous surveys in England [43]. Our study showed that students from low-income families were more prone to be distressed by psychological symptoms, which was in agreement with previous researches [44][45][46][47].…”
Section: Discussionsupporting
confidence: 93%
“…Four main themes arose from the analysis of the data 2 : the role of the GP; 3 clarity on help available; 4 getting advice and support; 5 and development needs. These themes are discussed narratively below:…”
Section: Methodsmentioning
confidence: 99%
“… 4 The rising prevalence and future implications highlight the importance of prevention and early intervention for child and adolescent mental health problems. 5 There has been much attention recently on the role of schools in providing mental health support, both in British government policy and research studies. 5 , 6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining which questions have value is more challenging, since allocating resources to any priority comes at the cost of divesting them from alternatives. For example, the focus on mechanistic approaches to psychological treatments could distract from other, pervasive determinants of mental disorders, like poverty (Deighton, et al, 2019), income inequality (Patel, et al, 2018) or living in a conflict zone (Jayasuriya, Jayasuriya, Tay, & Silove, 2016). Specifically, proposing a simple behavioral intervention like the Tetris game to tackle intrusive memories in refugees from warzones like Syria (Holmes, et al, 2017) might deflect from the disabling and enduring consequences of war-related trauma (Silove, et al, 2014).…”
Section: Are Research Decisions Based On Questions Relevant To Users mentioning
confidence: 99%